(untitled) (Journal of Civil Engineering Researchers, 2023)
Challenges in recent decades for humans and the rapidly changing planet. The increase in pollution and difficult access to energy despite the problems of war and political and economic disputes between countries and the rapid decrease in the amount of energy in the world, which with this growth rate, is a tangible danger for the whole world. It prompted scientists to look for new methods of energy production and consumption. In this article, we are looking for a topic of such projects, which are called zero energy buildings. As it is understood from the name of this project, the result of all energy consumption and production in these buildings must be zero or the energy production of the building should be more than its consumption, which is the concept of energy related to all the energy in the building such as thermal, electrical and ... which should be considered in the initial calculations and construction. For this purpose, this research, which is a descriptive analytical research, was conducted using library resources and electronic books and articles. We will review the execution and performance of architecture in zero energy building and concepts related to passive energy and building orientation for energy production, architectural components and materials of zero energy building, review the economic approach and leading challenges, construction and operation in connection with zero energy building. The results obtained from this research, zero energy buildings are faced with upcoming challenges such as technical knowledge, efficient and trained staff, and existing laws and regulations. Accordingly, the need to reduce energy consumption and optimize it is felt more and more. Zero energy buildings are the best solution to moderate energy consumption in housing. But reaching this goal has basic and fundamental needs that must be met.